KILANG BIOMASSA DARI LIMBAH PERTANIAN DAN PERKEBUNAN UNTUK PEMBANGUNAN BERKELANJUTAN - Muhammad Shalahuddin Rahmansyah; Sukma Hadi Anugerah; Lely Mardiyanti (Program Studi Teknik Lingkungan, Universitas Pembangunan Nasional Veteran Jawa Timur, 2021)
The agricultural and plantation waste biorefineries are the new strategy of the future to realize sustainability, but most are still in the conceptual stage. Biorefineries will allow communities to convert their agricultural and plantation waste into new value-added renewable energy, biochemical compounds, and fertilizers. Several biorefinery concepts of agricultural and plantation waste have been developed, but few have been commercially realized due to cost constraints and little reliance on new technologies, expected results, and profits, and reliability of operations. Therefore, this publication presented the concept of biorefineries in general, agricultural and plantation waste in Indonesia that has the potential to be used as raw materials for biorefineries and their manufacturing stages, the prospects of the products produced, and the results of the analysis on the challenges that will be faced in further development.